Innovative Physical Education Learning: A Collaborative Teamwork Model with Video Support - Yudaparmita, Gusti Ngurah Arya; Parwata, I Gusti Lanang Agung; Sudiana, I Ketut; Dharmadi, Made Agus (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
The problems experienced by students in physical education learning are not only limited to problems in aspects of knowledge, but also in aspects of attitudes and skills. The purpose of this study is to develop a physical education learning model based on collaborative teamwork learning assisted by learning videos. This type of research is development research using the ADDIE development model. The research subjects consisted of four groups, namely expert validity test subjects, small group test subjects, practicality test subjects. The data collection methods used in this study were observation, interviews, questionnaires, and documentation. The data collection instrument is in the form of a questionnaire sheet. This research data analysis technique uses qualitative and quantitative descriptive analysis. The results of this study resulted in a physical education learning model of health education materials based on team collaboration assisted by learning videos that met 5 criteria. The overall expert test assessment falls within the valid criteria. Based on the results of data analysis, practicality is stated to be practically applied to students in the learning process. The implication of this research is that the physical education learning model based on collaborative teamwork learning with the help of learning videos is effectively used in the learning process, overcoming problems in aspects of student knowledge, attitudes, and skills. It can be concluded that the physical education learning model of learning-based team collaboration learning-based health education materials assisted by learning videos can be used in learning.